Clinical usefulness of quantifying microbial load from diabetic foot ulcers: A multicenter cohort study. (July 2022) - Soldevila-Boixader, Laura; Mur, Isabel; Morata, Laura; Sierra, Yanik; Rivera, Alba; Bosch, Jordi; Montero-Saez, Abelardo; Fernández-Reinales, Alvaro J.; Martí, Sara; Benito, Natividad; Murillo, Oscar
Abstract: Aims: To evaluate if microbial load from diabetic foot ulcers (DFUs) can help in predicting outcomes. Methods: A multicenter prospective cohort study was performed in an outpatient setting (September 1, 2017-January 31, 2019) in diabetic patients with DFU. Quantitative cultures from DFU tissue biopsies at a baseline visit were obtained; high and low microbial loads were defined as ≥6 log CFU/mL and <6 log CFU/mL, respectively. Diagnosis of DFU infection was made and managed according to established guidelines. The outcome was evaluated at 6 month-visit as failure (persistence/new infection/amputation) or cure. Results: Out of 65 patients, 52 (80%) had long-standing DFUs (≥4 weeks), with high microbial load in 19 (29%). DFU infection (n = 24, 37%) was not associated with high microbial load in all patients but those with shorter DFU duration. Treatment failure occurred in 20/57 (35%) patients; high DFU microbial load was associated with worse outcome (n = 9/20, 45% failure rate, adjusted OR 4.69; 95% CI, 1.22–18.09; p = 0.03),  mainly due to the subgroup of patients with high microbial load and long-stand DFUs. Conclusions: Since patients with high microbial load had a worse outcome, quantitative cultures from DFUs can identify patients who would benefit from antibiotic therapy.